Performance Analysis of a Five-axis Linkage Hybrid Machine Tool - Caiyou Qin; Juan Huang; Xiaoru Li (Jixie chuandong)
Hybrid machine tool is a combination of series， parallel mechanism and robotics，which contains the advantages of them and used more and more widely in the manufacturing equipment for parts with complex structure. A five-axis linkage hybrid machine tool is proposed， and the realization and principle of manufacturing process and principles are analyzed. Based on the constraint of rod length in parallel modules， the kinematics model in machining process is established. Based on the velocity projection， the Jacobi matrix of parallel modules is solved. The dynamics model of the machine tool is established which based on the Lagrange equations and Jacobi matrix. Finally， the theoretical analysis results are calculated by Matlab. The required machine driving displacement， speed and force is being solved in the case of known machine tool cutting amount. Combined with kinematics results， the machine tool workspace is analyzed. The results show that the hybrid machine tool has good kinematics， dynamics and large workspace and other performance， and can meet the complex parts processing， but also provide a theoretical basis for the development of hybrid machine tool.